NCMA quaternary positive electrode material, preparation method thereof and all-solid-state battery
The radial NCMA quaternary cathode material was prepared by co-precipitation method and solid phase one-phase calcination method, and the cladding layer was formed by adhesion of acid phosphate, which solved the problem of interface failure of quaternary cathode material/sulfide electrolyte, and significantly improved electrochemistry Performance and cycle stability.
Patent Information
- Application Number
- CN202411291554.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing NCMA quaternary positive electrode materials have poor electrical performance in sulfide electrolyte all-solid state batteries, mainly due to the serious failure of the interface of the quaternary positive electrode materials/sulfide electrolyte, resulting in the impedance of Li+ transmission and poor interface stability.
The radial NCMA quaternary cathode material was prepared by co-precipitation method and solid phase primary calcination method, and a 10-50nm cladding layer was formed by acid phosphate adhesion and secondary calcination, thereby improving the surface characteristics and interface compatibility of the material.
Through directional growth and the design of the acid phosphate coating, the cracking of the positive electrode material during the long cycle is significantly reduced, the interface conductivity and stability are improved, and the electrochemical performance of the quadruple positive electrode material is improved.
Smart Images

Figure CN119400813A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to an NCMA quaternary positive electrode material and a preparation method thereof and an all-solid-state battery. Background Art
[0002] All-solid-state lithium batteries, due to their use of non-flammable solid electrolytes, are expected to solve the safety issues of traditional lithium batteries. At the same time, they simplify the battery structure and can achieve higher battery specific energy design, which has attracted widespread attention in recent years.
[0003] The electrical performance of all-solid-state lithium batteries is closely related to the solid electrolyte, cathode material, and the interface characteristics of the two. -2 S cm -1 ), sulfide is considered to be a promising solid electrolyte for all-solid-state lithium batteries. In addition, exploring cathode materials suitable for sulfide electrolyte solid-state battery systems is also particularly important for building all-solid-state lithium batteries with high specific energy and long life. Among them, high nickel materials, especially quaternary cathode materials LiNi x Co y Mn z Al 1-x-y-z O2(NCMA) is considered to have great application potential in sulfide electrolyte all-solid-state battery systems due to its advantages of high voltage, high specific capacity, long life and thermal stability that are superior to traditional ternary materials. However, due to the serious deterioration and failure of the quaternary cathode material / sulfide electrolyte interface during the charge and discharge process, the electrical performance of the quaternary cathode material in all-solid-state lithium batteries is far inferior to that of liquid lithium-ion batteries.
[0004] During battery preparation or charge-discharge cycles, due to the difference in chemical potential and electrochemical potential, side reactions will occur between the quaternary cathode material and the sulfide electrolyte, forming a high-impedance solid / solid interface layer that hinders Li + There are a lot of free alkaline impurities on the surface of quaternary cathode materials. These insulating substances greatly hinder ion transmission. In addition, due to the strong surface oxidation of quaternary cathode materials and the poor compatibility with sulfide electrolytes, the interface stability will be seriously reduced. Traditional cathode materials are composed of disordered primary particles. + During the repeated embedding and disembedding process, severe stress concentration is generated, causing severe cracking of the material after a long cycle, thereby inducing contact failure between material particles.
[0005] For example, CN 111640928A NCMA quaternary material and preparation method thereof, lithium battery positive electrode material and lithium battery, using NCMA as a substrate, obtains a coated quaternary positive electrode material by coating two metal oxides Co3O4 and V2O5. The cost is relatively high, the process steps are many, and after electrochemical testing, the capacity is not high enough and the cycle performance is poor, which is not conducive to industrial production. Summary of the invention
[0006] The main purpose of the present invention is to provide a NCMA quaternary positive electrode material and a preparation method thereof and an all-solid-state battery to solve the problem of poor electrical performance of the positive electrode material in the prior art in a sulfide electrolyte solid-state battery system.
[0007] The present invention is achieved by a method for preparing a NCMA quaternary positive electrode material, comprising the following steps:
[0008] Step 1, preparing NCMA precursor by coprecipitation method;
[0009] Step 2, preparing radial NCMA quaternary positive electrode material by solid phase primary calcination;
[0010] Step 3, acid phosphate attachment and secondary calcination are performed on the prepared radial NCMA quaternary positive electrode material to obtain the radial NCMA quaternary positive electrode material after acid phosphate attachment.
[0011] The chemical formula of the NCMA quaternary cathode material is LiNi w Co x Mn y Al z O2, wherein 0.88≤w≤0.95, 0.03≤x≤0.06, 0.01≤y≤0.03, 0.01≤z≤0.03, and w+x+y+z=1.
[0012] The mass ratio of the NCMA quaternary positive electrode material to the acid phosphate is 0.001-0.05:1, and the acid phosphate is Zr(HPO4)2·H2O.
[0013] The thickness of the coating layer of the radial NCMA quaternary positive electrode material is 10 to 50 nm.
[0014] In the step 3, the temperature of the second calcination is 400-600° C., the time of the second calcination is 5-10 hours, and the second calcination is carried out in an oxygen atmosphere.
[0015] The step 2 is: mixing the NCMA precursor with LiOH and a directional growth inducer to obtain a mixture; calcining the mixture for the first time to obtain a once-calcined material; cooling and crushing the once-calcined material to obtain a radial NCMA quaternary positive electrode material with a particle size of 6 to 20 μm; the molar ratio of the NCMA precursor, LiOH and the directional growth inducer is 1:1 to 1.06:0.001 to 0.01.
[0016] The directional growth inducing agent is WO3.
[0017] The mixing is dry mixing, the temperature of the first calcination is 700-850° C., the time of the first calcination is 10-20 hours, and the first calcination is carried out in an oxygen atmosphere.
[0018] The NCMA quaternary positive electrode material is prepared by the above preparation method.
[0019] An all-solid-state battery using the above-mentioned NCMA quaternary positive electrode material.
[0020] The advantages and technical effects of the present invention are as follows: The radially structured quaternary positive electrode material prepared by the present invention improves the interface failure of the quaternary positive electrode material / sulfide electrolyte, that is, by directional induction of the growth of the primary particles of the quaternary positive electrode material, making them tend to be consistent, thereby significantly reducing the cracking during the long cycle process. Introducing an acid phosphate coating layer on the surface of the high-nickel ternary layered oxide material to avoid its contact with the sulfide electrolyte can effectively inhibit the occurrence of side reactions. At the same time, the acid phosphate can effectively consume the alkaline impurities on the surface of the quaternary positive electrode material, thereby improving the conductivity of the surface layer of the quaternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the SEM of the NCMA quaternary positive electrode material prepared in Example 1 (a. surface morphology of the positive electrode material; b. cross-sectional morphology of the positive electrode material).
[0022] Figure 2 This is the SEM of the NCMA quaternary positive electrode material prepared in Comparative Example 1 (a. surface morphology of the positive electrode material; b. cross-sectional morphology of the positive electrode material). DETAILED DESCRIPTION
[0023] The preparation method of the NCMA quaternary positive electrode material of the present invention comprises the following steps:
[0024] Step 1, preparing NCMA precursor by coprecipitation method;
[0025] Step 2, preparing radial NCMA quaternary positive electrode material by solid phase primary calcination;
[0026] Step 3, acid phosphate attachment and secondary calcination are performed on the prepared radial NCMA quaternary positive electrode material to obtain the radial NCMA quaternary positive electrode material after acid phosphate attachment.
[0027] The chemical formula of the NCMA quaternary cathode material is LiNi w Co x Mn y Al z O2, wherein 0.88≤w≤0.95, 0.03≤x≤0.06, 0.01≤y≤0.03, 0.01≤z≤0.03, and w+x+y+z=1.
[0028] The mass ratio of the NCMA quaternary positive electrode material to the acid phosphate is 0.001-0.05:1, and the acid phosphate is Zr(HPO4)2·H2O.
[0029] The thickness of the coating layer of the radial NCMA quaternary positive electrode material is 10 to 50 nm.
[0030] In the step 3, the temperature of the second calcination is 400-600° C., the time of the second calcination is 5-10 hours, and the second calcination is carried out in an oxygen atmosphere.
[0031] The step 2 is: mixing the NCMA precursor with LiOH and a directional growth inducer to obtain a mixture; calcining the mixture for the first time to obtain a once-calcined material; cooling and crushing the once-calcined material to obtain a radial NCMA quaternary positive electrode material with a particle size of 6 to 20 μm; the molar ratio of the NCMA precursor, LiOH and the directional growth inducer is 1:1 to 1.06:0.001 to 0.01.
[0032] The directional growth inducing agent is WO3.
[0033] The mixing is dry mixing, the temperature of the first calcination is 700-850° C., the time of the first calcination is 10-20 hours, and the first calcination is carried out in an oxygen atmosphere.
[0034] The NCMA quaternary positive electrode material is prepared by the above preparation method.
[0035] An all-solid-state battery using the above-mentioned NCMA quaternary positive electrode material.
[0036] The present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art will easily identify various non-critical parameters that can be changed or altered to produce substantially the same result.
[0037] Example 1
[0038] A method for preparing a NCMA quaternary positive electrode material comprises the following steps:
[0039] The NCMA precursor (molar ratio: Ni:Co:Mn:Al=88:6:3:3), LiOH, and directional growth inducing agent WO3 are directly stirred and mixed in a powder high-speed mixer at a molar ratio of 1:1.05:0.003 to obtain a mixture. The mixture is calcined in a roller kiln at 765°C in an oxygen atmosphere for 15 hours, and then cooled, crushed and sieved to obtain a radial NCMA quaternary positive electrode material with a particle size of 12.5 μm. The chemical formula of the NCMA quaternary positive electrode material is LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2. Since the W element content is extremely small, it is not represented in the chemical formula.
[0040] The radial NCMA quaternary positive electrode material and Zr(HPO4)2·H2O were fluidized bed coated at a mass ratio of 1:0.005, so that Zr(HPO4)2·H2O was uniformly attached to the surface of the NCMA quaternary positive electrode material to obtain the attached material. The attached material was calcined at 500°C in an oxygen atmosphere for 8 hours, cooled, crushed, sieved, and demagnetized to obtain the NCMA quaternary positive electrode material. The thickness of the coating layer of the NCMA quaternary positive electrode material is 31nm.
[0041] Example 2
[0042] Compared with Example 1, the NCMA quaternary positive electrode material and Zr(HPO4)2·H2O were dry mixed at a mass ratio of 1:0.001, and the other conditions remained unchanged.
[0043] A method for preparing a NCMA quaternary positive electrode material comprises the following steps:
[0044] The NCMA precursor (molar ratio: Ni:Co:Mn:Al=88:6:3:3), LiOH, and directional growth inducing agent WO3 are directly stirred and mixed in a powder high-speed mixer at a molar ratio of 1:1.05:0.003 to obtain a mixture. The mixture is calcined in a roller kiln at 765°C in an oxygen atmosphere for 15 hours, and then cooled, crushed and sieved to obtain a radial NCMA quaternary positive electrode material with a particle size of 12.3 μm. The chemical formula of the NCMA quaternary positive electrode material is LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2. Since the W element content is extremely small, it is not represented in the chemical formula.
[0045] The radial NCMA quaternary positive electrode material and Zr(HPO4)2·H2O were fluidized bed coated at a mass ratio of 1:0.002, so that Zr(HPO4)2·H2O was uniformly attached to the surface of the NCMA quaternary positive electrode material to obtain the attached material. The attached material was calcined at 500°C in an oxygen atmosphere for 8 hours, cooled, crushed, sieved, and demagnetized to obtain the NCMA quaternary positive electrode material. The thickness of the coating layer of the NCMA quaternary positive electrode material is 15nm.
[0046] Example 3
[0047] Compared with Example 1, the components of the NCMA quaternary positive electrode material are designed to be LiNi 0.90 Co 0.05 Mn 0.03 Al 0.02 O2
[0048] A method for preparing a NCMA quaternary positive electrode material comprises the following steps:
[0049] The NCMA precursor (molar ratio: Ni:Co:Mn:Al=90:5:3:2) was directly stirred and mixed with LiOH and directional growth inducing agent WO3 in a powder high-speed mixer at a molar ratio of 1:1.05:0.003 to obtain a mixture. The mixture was calcined in a roller kiln at 765°C in an oxygen atmosphere for 15 hours, and then cooled, crushed and sieved to obtain a NCMA quaternary positive electrode material with a particle size of 12.7 μm. The chemical formula of the NCMA quaternary positive electrode material is LiNi 0.90 Co 0.05 Mn 0.03 Al 0.02 O2.
[0050] The radial NCMA quaternary positive electrode material and Zr(HPO4)2·H2O were fluidized bed coated at a mass ratio of 1:0.005, so that Zr(HPO4)2·H2O was uniformly attached to the surface of the NCMA quaternary positive electrode material to obtain the attached material. The attached material was calcined at 500°C in an oxygen atmosphere for 8 hours, cooled, crushed, sieved, and demagnetized to obtain the NCMA quaternary positive electrode material. The thickness of the coating layer of the NCMA quaternary positive electrode material is 30nm.
[0051] Example 4
[0052] Compared with Example 1, the doping ratio of the directional growth inducing agent is designed to be 1:0.005, and the other conditions remain unchanged.
[0053] A method for preparing a novel quaternary cathode material for an all-solid-state battery comprises the following steps:
[0054] The NCMA precursor (molar ratio: Ni:Co:Mn:Al=88:6:3:3), LiOH, and directional growth inducing agent WO3 are directly stirred and mixed in a powder high-speed mixer at a molar ratio of 1:1.05:0.005 to obtain a mixture. The mixture is calcined in a roller kiln at 765°C in an oxygen atmosphere for 15 hours, and then cooled, crushed and sieved to obtain a radial NCMA quaternary positive electrode material with a particle size of 12.3 μm. The chemical formula of the NCMA quaternary positive electrode material is LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2. Since the W element content is extremely small, it is not represented in the chemical formula.
[0055] The radial NCMA quaternary positive electrode material and Zr(HPO4)2·H2O were fluidized bed coated at a mass ratio of 1:0.005, so that Zr(HPO4)2·H2O was uniformly attached to the surface of the NCMA quaternary positive electrode material to obtain the attached material. The attached material was calcined at 500°C in an oxygen atmosphere for 8 hours, cooled, crushed, sieved, and demagnetized to obtain the NCMA quaternary positive electrode material. The thickness of the coating layer of the NCMA quaternary positive electrode material is 30nm.
[0056] Comparative Example 1
[0057] The NCMA precursor (molar ratio: Ni:Co:Mn:Al=88:6:3:3) and LiOH were directly stirred and mixed in a powder high-speed mixer at a molar ratio of 1:1.05 to obtain a mixture. The mixture was calcined in a roller kiln at 765°C in an oxygen atmosphere for 15 hours, and then cooled, crushed and sieved to obtain a disorderly stacked NCMA quaternary positive electrode material with a particle size of 12.5 μm. The chemical formula of the NCMA quaternary positive electrode material is LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2.
[0058] All-solid-state battery production: The NCMA quaternary positive electrode materials prepared in the above-mentioned Examples 1-4 and Comparative Example 1 were respectively mixed with Li 10 GeP2S 12 The sulfide electrolyte was ground and mixed evenly in a mass ratio of 7:3 to prepare a composite positive electrode powder. 10 GeP2S 12100g of sulfide electrolyte is placed in a solid-state battery mold and molded under a pressure of 10MPa. The negative electrode uses Li-In alloy. When assembling the battery, weigh 10mg of the composite positive electrode powder, assemble the battery in the order of composite stainless steel sheet-negative electrode-electrolyte-composite positive electrode-stainless steel sheet, extrude it at a pressure of 15MPa, and finally tighten it with screws. The assembly process is carried out in a glove box filled with argon. The electrical performance test is also carried out in the glove box, using the Xinwei battery test system at 35°C, with a test voltage range of 2.1 to 3.68V; the first discharge capacity, efficiency and 100-week capacity retention rate are tested, and the test results are listed in Table 1.
[0059] Table 1 Electrical performance test data
[0060]
[0061] It can be seen from the data in Table 1 that compared with Comparative Example 1, it can be seen that the capacity and cycle of the NCMA quaternary positive electrode materials in Examples 1 to 5 are better. This is mainly because the residual lithium is eliminated through a chemical reaction after Zr(HPO4)2·H2O coating, thereby improving the conductivity of the interface between the NCMA quaternary positive electrode material and the sulfide electrolyte; on the other hand, the coating layer effectively prevents the side reactions caused by direct contact between the high-nickel layered oxide and the sulfide, thereby improving the material specific capacity; at the same time, the radial structure effectively prevents internal cracking of the positive electrode material, inhibits contact failure, and improves the material cycle performance.
[0062] The present invention utilizes Zr(HPO4)2·H2O coating to eliminate the characteristics of residual lithium through chemical reaction, improve the ion transportability of the material surface, and thus effectively improve the electrochemical performance of the material. Based on the characteristic that Zr(HPO4)2·H2O can generate a stable and uniform coating layer on the surface of the material, fluidized bed coating and high-temperature solid phase method are used to generate the coating layer to solve the problem of poor interface compatibility between NCMA and sulfide electrolyte. Zr(HPO4)2·H2O is used as a coating layer, and both Zr and P elements can be introduced at the same time. In addition, the material is evenly dispersed during the preparation process, and the cost is low. Therefore, it can be prepared in batches, which is suitable for industrial production.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a NCMA quaternary positive electrode material, characterized in that: The following steps are involved: Step 1, preparing NCMA precursor by coprecipitation method; Step 2, preparing radial NCMA quaternary positive electrode material by solid phase primary calcination; Step 3, acid phosphate attachment and secondary calcination are performed on the prepared radial NCMA quaternary positive electrode material to obtain the radial NCMA quaternary positive electrode material after acid phosphate attachment.
2. The method for preparing the NCMA quaternary positive electrode material according to claim 1, characterized in that: The chemical formula of the NCMA quaternary cathode material is LiNi w Co x Mn y Al z O2, wherein 0.88≤w≤0.95, 0.03≤x≤0.06, 0.01≤y≤0.03, 0.01≤z≤0.03, and w+x+y+z=1.
3. The method for preparing the NCMA quaternary positive electrode material according to claim 1, characterized in that: The mass ratio of the NCMA quaternary positive electrode material to the acid phosphate is 0.001-0.05:1, and the acid phosphate is Zr(HPO4)2·H2O.
4. The method for preparing the NCMA quaternary positive electrode material according to claim 1, characterized in that: The thickness of the coating layer of the radial NCMA quaternary positive electrode material is 10 to 50 nm.
5. The method for preparing the NCMA quaternary positive electrode material according to claim 1, characterized in that: In the step 3, the temperature of the second calcination is 400-600° C., the time of the second calcination is 5-10 hours, and the second calcination is carried out in an oxygen atmosphere.
6. The method for preparing the NCMA quaternary positive electrode material according to claim 1, characterized in that: The step 2 is: mixing the NCMA precursor with LiOH and a directional growth inducer to obtain a mixture; calcining the mixture for the first time to obtain a once-calcined material; cooling and crushing the once-calcined material to obtain a radial NCMA quaternary positive electrode material with a particle size of 6 to 20 μm; the molar ratio of the NCMA precursor, LiOH and the directional growth inducer is 1:1 to 1.06:0.001 to 0.
01.
7. The method for preparing the NCMA quaternary positive electrode material according to claim 6, characterized in that: The directional growth inducing agent is WO3.
8. The method for preparing the NCMA quaternary positive electrode material according to claim 6, characterized in that: The mixing is dry mixing, the temperature of the first calcination is 700-850° C., the time of the first calcination is 10-20 hours, and the first calcination is carried out in an oxygen atmosphere.
9. The NCMA quaternary positive electrode material obtained by the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: The NCMA quaternary positive electrode material of claim 9 is used.
Citation Information
Patent Citations
NCMA quaternary system material and preparation method thereof, lithium battery positive electrode material and lithium battery
CN111640928A
Surface modification lithium ion battery high-nickel laminated cathode material and preparation method thereof
CN107221645A
Lithium titanium scandium phosphate modified lithium ion battery positive electrode material and preparation method thereof
CN111987309A
High-nickel positive electrode material, preparation method thereof and lithium ion secondary battery
CN112382741A
Positive electrode material, preparation method therefor, and lithium ion secondary battery
US20230077131A1